First report of lepidopteran insects from the Trang An Landscape Complex, Ninh Binh Province, with two new country records - Nhi, Pham Thi; Tru, Hoang Vu; Nam, Nguyen Hai (Academia Journal of Biology, 2019)
Based on the material collected from the field surveys in 2017–2018, we report the first list of lepidopteran insects from the Trang An Landscape Complex, Ninh Binh Province. A total of 167 species including 62 butterflies and 105 moths have been recorded, in that two species, Celerena signata Warren, 1898 and Nygmia plana (Walker, 1856) are recorded for the first time from Vietnam.